Analysis of Determinants of Motivation and Regulatory Understanding on the Speed of Covid-19 Claim Services in Sidoarjo Regency Hospital - Rahmadi, Syamsu; Yuly Peristiowati; Agusta Dian Ellina (Journal Of Nursing Practice, 2023)
Background: There is a file of disputed Covid-19 claims which is an indication of less than optimal employee performance. The claim rate of Covid-19 services is inseparable from the influence of the service revenue rate, the service revenue provided as well as motivation and regulation understanding of COVID-19 service. Purpose: This study aims to analyze the effect of services revenue rate, service revenue, work motivation, and regulations understanding on the claim rate, the effect of the service revenue rate and services revenue received on work motivation, the influence of the service revenue rate of services and services revenue received on regulation understanding. Methods: This research is a correlation research with the cross sectional method. The sample used was RSUD employees who were involved in the process of filling in the Covid-19 claim file from the start until the claim was received, 150 people, with the proportional random sampling  technique. Data collecting techniques used in this study is a questionnaire, which was then analyzed by Partial Least Square analysis. Results: The service revenue rate has no significant effect on the claim of Covid-19 service rate, while service revenue, motivation, and regulations understanding have a significant effect on the Covid-19 claims rate. Meanwhile, services revenue rate and the service revenue significantly influences Human Resource motivation, the services revenue rate does not significantly affect regulations understanding, while services revenue has a significant effect on regulations understanding. Conclusion: Services rate is not able to encourage the claims rate. The service revenue, HR motivation, and regulations understanding are variables that can support the claims rate. The services revenue rate and the service revenue can trigger HR motivation. The rate at which services are revenued is not a variable capable of supporting understanding regulatory. The service rate encourage the regulation understanding.